PENGARUH KEMATANGAN EMOSI TERHADAP PERILAKU SEKS BEBAS PADA REMAJA DI SMA SWASTA PENCAWAN MEDAN - Indo Mora; Siska Dwi Ningsih; Laksana Tobing; Richa Margaretha Simbolon (Psikologi Universitas Sari Mutiara Indonesia, 2019)
This research aims to determine the effect of emotional maturity on free sex behavior conducted by adolescents in Pencawan high school Medan. This research uses a quantitative approach. Data collection is done at Pencawan high school Medan. Research subjects are high school students with sample size 56 students. The sampling technique of this research is purposive sampling. Data collection tools such as the scale of emotional maturity and the scale of free sex behavior. Test the validity of the instrument using Corrected Item-Total Corelation test. The instrument reliability test is calculated using the Cronbach Alpha formula. Data analysis using simple regression technique on hypothesis test with significance value 5%. The results showed that there is a significant influence between emotional maturity on free sex behavior in adolescents in Pencawan high school Medan with effective contribution of 24.3%. The equation of the regression line is Y = 102.714 + (- 0.689) X. The conclusion of this study is the emotional maturity of adolescents in Pencawan high school Medan is in the high category, free sex behavior in adolescents in Pencawan high school Medan is in the low category, and emotional maturity can predict free sex behavior in adolescents in Pencawan high school Medan.